The Effectiveness Of Online Physical Education Learning During Covid-19 Pandemic On Students Of Sma Plus Alfatimah Bojonegoro - Mohamad Da'i; Hilmy Aliriad (Universitas Bengkulu, 2021)
This research aims to determine the effectiveness of Online Learning Physical Education in Times of Pandemic COVID-19 on High School Students Plus Al Fatimah Bojonegoro. The type of research used is descriptive quantitative. The method used is a survey using a questionnaire instrument. The population in this study were students of class X, XI and XII with a sample of 100 students. The analysis technique uses descriptive quantitative analysis techniques with percentages. The results of this study indicate that the responses of students regarding online learning during the pandemic with the very effective category are 21%, the effective category is 74%, the less effective category is 5%, and the ineffective category is 0%. Thus, it can be concluded that the effectiveness of learning Physical Education, Sports and Health in the network (online) during the covid pandemic based on the views of SMA Plus Al Fatimah Bojonegoro students is included in the effective category.